Game Edukasi Pembelajaran IPA Siswa Kelas 6 SD Berbasis Android "Science Stump" - Prasetyo, Bagus; Sugiyanto, Sigit (Jurnal Ilmu Komputer dan Sistem Informasi (JIKOMSI), 2023)
As technology develops, we often find children who prefer playing with cell phones rather than holding books. This certainly affects their learning motivation. Children in grade 6 of elementary school tend to have low literacy levels, and they prefer exploring exciting and fun activities rather than reading books. To overcome this problem, the author designed an educational game called Science Stump, combining technology and education. This educational game was created using the Game Design Life Cycle (GDLC) method through the initiation, pre-production, production, testing and release stages. Science Stump was designed using Construct 3 with the help of Canva in creating the layout. After going through black box testing and interviews with 20 students as a sample, the final results of this research were successful and successfully launched. Keywords: teaching media, educational game, Science, puzzle, Construct 3